Johnston, Michael. 2023. The Middle English Book: Scribes and Readers, 1350–1500. Oxford: Oxford University Press. Pp. xvi + 288. ISBN 9780192871770. - Cosima Gillhammer (SELIM, 2025)
Book review of Johnston, Michael. 2023. The Middle English Book: Scribes and Readers, 1350–1500. Oxford: Oxford University Press. Pp. xvi + 288. ISBN 9780192871770.